2002
DOI: 10.1007/s00268-002-6615-y
|View full text |Cite
|
Sign up to set email alerts
|

Familial Nonmedullary Thyroid Carcinoma Characterized by Multifocality and a High Recurrence Rate in a Large Study Population

Abstract: First-degree relatives of persons with thyroid cancer are known to be at relatively high risk for the disease. To better understand the clinicopathologic characteristics of familial nonmedullary thyroid carcinoma (FNMTC), we carried out a retrospective study in which we identified individuals treated at our institution who had at least one first-degree relative with the disease. We used data obtained from our patient records to compare the features of 258 cases of the disease with the features of sporadic papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
201
6
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(232 citation statements)
references
References 28 publications
16
201
6
9
Order By: Relevance
“…Although some studies have reported a less favourable prognosis for FNMTC (3,16,17,18,19,20,21), others did not verify this (1,22,23,24,25), and therefore, the biological and clinical behaviour of this familial disease, as compared with the much more frequent sporadic forms, remains a matter of controversy. Furthermore, data on molecular biomarkers, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Although some studies have reported a less favourable prognosis for FNMTC (3,16,17,18,19,20,21), others did not verify this (1,22,23,24,25), and therefore, the biological and clinical behaviour of this familial disease, as compared with the much more frequent sporadic forms, remains a matter of controversy. Furthermore, data on molecular biomarkers, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…According to the largest of such studies published to date, the family risk ratio of PTC in first-degree relatives of a PTC proband is as high as 8-12, being the highest of all cancers (4-6). Some 5-10% of probands with PTC have at least one first-or second-degree relative with PTC (7,8). However, remarkably, large families with multiple cases of PTC are rare and often do not display Mendelian inheritance.…”
mentioning
confidence: 99%
“…Además, existe agregación familiar de MCT, lo cual también se ve en la patología autoinmunitaria y podría constituir otro factor de error en la interpretación de la patología del paciente. La presencia de tiroiditis se ha planteado como un factor de mayor agresividad en dichos tumores, es relevante hacer notar que el motivo de estudio de esta familia (sólo la presencia de un familiar afectado) no es el estándar planteado hasta el momento 14,15 .…”
Section: Discussionunclassified